A Case-Control Study of Contextual Factors for SARS-CoV-2 Transmission - Leite, A (2021)
Background: Knowledge on the settings and activities associated with a higher risk of SARS-CoV-2 transmission is essential to inform decision-making. We thus designed a case-control study to identify relevant settings for community transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in Portugal. Methods: We evaluated 1,088 cases, identified through the national surveillance system, and 787 community controls, recruited using random digit dialing. Sociodemographic characteristics, individual protective measures, and activities or visited settings were obtained through telephone interview. We report sex-, age-, education-, and citizenship-adjusted odds ratios (aOR) with 95% confidence intervals (95% CI). Results: Household overcrowding (aOR = 1.47; 95% CI 1.14-1.91) and work in senior care (4.99; 1.30-33.08) increased while working remotely decreased the risk of infection (0.30; 0.22-0.42). Going to restaurants/other dining spaces (0.73; 0.59-0.91), grocery stores (0.44; 0.34-0.57) or hair salons (0.51; 0.39-0.66), or the use of public transportation did not present a higher risk of infection (0.98; 0.75-1.29), under existing mitigation strategies. Lower education ( ≤ 4 years vs. tertiary education: 1.79; 1.33-2.42) and no Portuguese citizenship (5.47; 3.43-9.22) were important risk factors. Conclusions: The utilization of public transportation, restaurants, and commercial spaces was not associated with increased risk of infection, under capacity restrictions, physical distancing, use of masks, and hygiene measures. Overcrowding, foreign citizenship, low education and working on-site were positively associated with SARS-CoV-2 infection.